Sampling Risks and Audit Consequences Under Alternative Testing Approaches. - Kiger, Jack E.; Beck, Paul J.; Solomon, Ira (The Accounting Review, 1985)
Abstract ABSTRACT: This paper investigates the relationship between sampling risks and audit consequences under error and audit value projection testing approaches. The latter approach typically is presented in auditing textbooks in connection with classical variables sampling, while the former approach is shown to underlie both dollar-unit sampling methods (in which an upper precision limit for monetary error is computed) and statistical compliance testing methods. In particular, we demonstrate analytically that error projection approaches implicitly test null hypotheses which effectively are equivalent to an alternative hypothesis underlying audit value projection. We also present outcome matrices to identify the effect of such hypothesis interchange on the audit consequences of sampling risks, and thus provide a basis for clarifying sampling risk discussions in textbooks and the recently issued Audit and Accounting Guide: Audit Sampling.